Learning styles and strategies for language use in the context of academic reading tasks. (June 2015) - Uhrig, Karl
Abstract: Although research has indicated that learning styles influence language learning strategy choices, many studies regard the two in isolation from each other. Additionally, most research in these areas is based on large-scale survey instruments that are removed from the context of language learning and use. This study represents an attempt to resolve these issues through two case studies of international students' learning strategy use on tasks in professional graduate programs in the US. Data gathered from interviews, documents, and task logs were analyzed first for strategy use on specific tasks, then for patterns that may indicate consistency according to learning style. The findings indicate that the participants' learning styles provide more predictability in strategy use on particular tasks than other factors such as discipline.